Answers

2015-07-01T08:56:05+08:00
X2-6x-72=0

group the terms containing x 
(x2-6x)-72=0

complete the square 
(x2-6x+__)    get the half of 6 .. the answer is 3 .. square the 3 the answer is 9 ..
(x2-6x+9) the last term should be always positive .. 
(x2-6x+9)-72-9 ..insert the 9 but it should be negative 

express as a square of binomial 
(x-3)2 -81=0

solve by extracting the square root 
you have to square root equation above 
(x-3)2 -81=0

x-3=positive negative 9 ..transpose the 3 .. it will be negative 3

x=9-3       x=3
x=-9-3      x=-12

hope i can help
0